Comparative Histological and Histochemical Studies on Epididymis of Aseel and Vanaraja Breeds of Poultry - Deshmukh, S. K.; Ingole, S. P.; Chaurasia, D.; Karmore, S. K.; Sinha, B. (Indian Journal of Veterinary Anatomy, 2015)
A comparative histological and histochemical study was conducted in grower and adult poultry birds of Aseel and Vanaraja breeds. The epididymis consisted of proximal and distal efferent ductules, connecting ductules and ductus epididymidis. The lining epithelium of the efferent ductules was simple columnar to pseudostratified columnar in growers, while in adult it was ciliated pseudostratified columnar. The mucosal folds in the efferent ductules were leaf to tongue shaped, while in connecting ductule the mucous membrane was not folded. The height of epithelium and diameter of efferent ductules, connecting ductules and ductus epididymidis was significantly lower in Aseel than Vanaraja breed of poultry. Periodic acid Schiff’s and Alcian blue - periodic acid Schiff’s activity was weaker in epididymis of Aseel as compared to that of Vanaraja.